Mongolia: The Rise and Travails of a Deviant Democracy - Fritz, V. (2012)
In the 1990s, Mongolia surprisingly became a new democracy - surprising because of its low income levels and geographic distance from established democracies. This article explores the country's transition process and the reasons for its successful democratization 'against the odds'. It argues that Mongolia benefited from a benign combination of supporting factors, as well as the absence of obstacles that have plagued potential transitions elsewhere. External influences - such as, 'contagion' from Central and Eastern Europe and dependency on foreign donors who favoured democracy and were active in democracy promotion - form an important aspect of the favourable constellation during transition. The second part of the article considers the period of democratic consolidation. Electoral democracy had become the 'only game in town' by the late 1990s in Mongolia. Elections have been held regularly, leading to several turnovers in power. Nonetheless, electoral democracy - combined with substantial if still imperfect civil and political liberties - has fallen short in generating effective accountability. Like many new democracies in poor countries elsewhere, Mongolia is prone to socio-economic shocks, and has experienced an increase in corruption and rent-seeking. In such a context, electoral democracy on its own does not appear to generate a stable, self-reinforcing equilibrium. In conclusion, democracy in Mongolia endures, but it is troubled.